2019
DOI: 10.3390/nu11071496
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Ingestion Inhibits Endurance Exercise-Induced IL-6 Producing Macrophage Infiltration in Mice Muscle

Abstract: Background: Carbohydrate (CHO) supplementation during exercise attenuates exercise-induced increases in plasma Interleukin (IL)-6 concentration. However, the effects of CHO supplementation on muscle IL-6 production during endurance exercise is controversial. The purpose of this study was to investigate the effects of CHO supplementation on muscle IL-6 production during endurance exercise with a special focus on the IL-6 producing cells. Methods: C57BL/6J mice were divided into three groups—sedentary with water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…It may affect the normal patterns of children and adolescents growth 2 . Obesity among children and adolescents is continuing to rise and reach up to 18% of children and adolescents aged [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in 2016 according to the World Health Organization (WHO) 3 . The aetiology of obesity is multimodal and multifactorial, which makes it difficult to identify causative and contributing factors 4 .…”
Section: Ijpsr (2021) Volume 12 Issue 3 (Research Article)mentioning
confidence: 99%
See 1 more Smart Citation
“…It may affect the normal patterns of children and adolescents growth 2 . Obesity among children and adolescents is continuing to rise and reach up to 18% of children and adolescents aged [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in 2016 according to the World Health Organization (WHO) 3 . The aetiology of obesity is multimodal and multifactorial, which makes it difficult to identify causative and contributing factors 4 .…”
Section: Ijpsr (2021) Volume 12 Issue 3 (Research Article)mentioning
confidence: 99%
“…IL-6 is a pleiotropic, multifunctional immunoregulatory cytokine that was first described as a B cell stimulatory factor 2 that enhances antibody production by activated B cells 16 . IL-6 is secreted by macrophages, adipose tissue, contracting skeletal muscles, and many other sources 17 . Several studies suggested an important role for IL-6 in glucose metabolism and fat metabolism by a lipolytic action with an antiobesity effect 18 .…”
Section: Ijpsr (2021) Volume 12 Issue 3 (Research Article)mentioning
confidence: 99%
“…We further assessed the synergistic effect of RT and CaHMB on cytokines related to fat metabolism in skeletal muscle and adipose tissue. It is important to point out that cytokine expression has been reported to be different between gastrocnemius and soleus muscles [ 46 ]. Furthermore, the secretion of FNDC-5 is around 40% higher in slow-oxidative fibre-type muscle (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that increased levels of IL-6 in the absence of exercise may be directly related to a higher degree of physical inactivity and metabolic syndrome (Bruun et al, 2006;Fischer et al, 2007). This "contradictory action" of IL-6 occurs because this interleukin can be produced not only by the immune system cells, but also by different tissues such as adipocytes (Coppack, 2001;Lyngsø et al, 2002), and muscle fibers through the initial infiltration of macrophages in the muscle tissue (Tominaga et al, 2019) or by the subsequent production of this interleukin by myoblasts (Gallucci et al, 1998;Pillon et al, 2013), thus triggering systemic pro-inflammatory (Coppack, 2001) or anti-inflammatory (Gallucci et al, 1998;Pillon et al, 2013) effects, respectively.…”
Section: Interleukin-6mentioning
confidence: 99%
“…Despite lacking recent original studies characterizing the biomolecular mechanisms behind the elevations of IL-6 in muscle fibers, some synergistic action between the infiltration of immune cells mediated by the practice of physical exercise in muscle tissue has been proposed as a determining factor for the regulation of muscle damage and inflammation (Gallucci et al, 1998;Kawanishi et al, 2016;Tominaga et al, 2019). In this context, the total plasma level of IL-6 can also be partially altered by immunological cells from the innate immune system (such as macrophages and neutrophils), as well as from the adaptive immune system (such as T and B cells) (Nielsen et al, 1996), depending on the training stimulus performed, ideally inducing transient pro-inflammatory effects, with a posterior anti-inflammatory response (Kawanishi et al, 2016).…”
Section: Interleukin-6mentioning
confidence: 99%